Supporting the Sexual Rights of Women Living With HIV: A Critical Analysis of Sexual Satisfaction and Pleasure Across Five Relationship Types. Issue 9 (22nd November 2018) - Carter, Allison; Greene, Saara; Money, Deborah; Sanchez, Margarite; Webster, Kath; Nicholson, Valerie; Brotto, Lori A.; Hankins, Catherine; Kestler, Mary; Pick, Neora; Salters, Kate; Proulx-Boucher, Karène; et al.
Abstract : In the context of human immunodeficiency virus (HIV), a focus on protecting others has overridden concern about women's own sexual well-being. Drawing on feminist theories, we measured sexual satisfaction and pleasure across five relationship types among women living with HIV in Canada. Of the 1, 230 women surveyed, 38.1% were completely or very satisfied with their sexual lives, while 31.0% and 30.9% were reasonably or not very/not at all satisfied, respectively. Among those reporting recent sexual experiences ( n = 675), 41.3% always felt pleasure, with the rest reporting usually/sometimes (38.7%) or seldom/not at all (20.0%). Sex did not equate with satisfaction or pleasure, as some women were completely satisfied without sex, while others were having sex without reporting pleasure. After adjusting for confounding factors, such as education, violence, depression, sex work, antiretroviral therapy, and provider discussions about transmission risk, women in long-term/happy relationships (characterized by higher levels of love, greater physical and emotional intimacy, more equitable relationship power, and mainly HIV-negative partners) had increased odds of sexual satisfaction and pleasure relative to women in all other relational contexts. Those in relationships without sex also reported higher satisfaction ratings than women in some sexual relationships. Findings put focus on women's rights, which are critical to overall well-being.